Organization Management - Dynamic Creative Team Coordination - Georgiades, Stavros (Edition Digital Science - Research,, 2022)
This open access book, through an in-depth process study of the interactions of two creative groups (film production crew) in temporary organizations during two media projects, explores how a team developmental process unfolds and proposes a model illustrating how the groups repeatedly change formation so that individuals can manage job interdependencies and new issues arising while developing, building up, and synthesizing new ideas into a final creative solution. This theory on creative group dynamic coordination builds theory on how and why creative groups coordinate, challenges assumptions about the role of formal structures and informal practices by demonstrating how the two dynamically interact and complement each other to facilitate coordination via the emergence of what one would expect to be "un-coordinated methods", and provides an alternative perspective to the stages the groups have to go through by emphasizing a cyclical and not a linear team developmental process. About the author Stavros Georgiades is Professor W2 of Management at the Stuttgart Media University (Visiting Post), Assistant Professor of Management at Frederick University, a research collaborator of the University of Digital Sciences Berlin and the founder of the Anagnorisis Institute of Media Management (AIMM). He holds a PhD in Management from the Henley Business School, University of Reading, UK. His research focuses on media employee engagement and creativity, team coordination and adaptation in media settings, and digital entrepreneurship.